ENHANCING PROBLEM-SOLVING SKILLS THROUGH NUMERACY INSTRUMENT DESIGN: INCORPORATING PANDEGLANG’S LOCAL WISDOM IN GEOMETRY CONTENT - Isnaintri, Endah; Yuhana, Yuyu; Fatah, Abdul (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
Problem solving is a crucial aspect of the education curriculum, as it reflects the skills expected to be possessed by students. Indicating that the majority of students face difficulties in this process. Studies also indicate that numeracy literacy plays a significant role in enhancing mathematical problem-solving skills. This research aims to develop a numeracy literacy assessment that integrates Pandeglang Regency's local knowledge, with a particular emphasis on geometry, to enhance the mathematical problem-solving abilities of Grade IX. This study fits into the Tessmer formative research model, which is related to the category of development research. The study involved 35 ninth-grade students from MTsN 2 Pandeglang as participants. Various tools were used to gather data, such as validation sheets, interview guidelines, and numeracy literacy tests inspired by local knowledge in the Pandeglang Regency. The analysis process included assessing these tools' effectiveness, reliability, and precision through expert assessments and statistical methods. The study's conclusions show that the developed test's quality comprises moderate difficulty for each of the three items, good validity, and satisfactory item discrimination.